1989
DOI: 10.1111/j.1151-2916.1989.tb06206.x
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Fine, Spherical Yttria‐Stabilized Zirconia by the Spray‐Pyrolysis Method

Abstract: Fine yttria-stabilized zirconia powders were prepared by the spray pyrolysis of aqueous solutions of Zr 0 C 1 -8 H 0 and Y ( N 0 , J3. 5 H 0 (3 mol%). An appropriate thermal treatment resulted in slightly porous spherical particles with a narrow size distribution. The sintering ability of these powders was evaluated. [

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(20 citation statements)
references
References 5 publications
0
16
1
1
Order By: Relevance
“…In contrast to previous literature [8,10], powder analyses showed that the spheres had a core-shell structure, with a hard exterior and porous interior. Such hollow structures have not been reported previously but are theoretically highly suitable for TBCs due to improved heat insulation capabilities.…”
Section: Introductioncontrasting
confidence: 45%
See 1 more Smart Citation
“…In contrast to previous literature [8,10], powder analyses showed that the spheres had a core-shell structure, with a hard exterior and porous interior. Such hollow structures have not been reported previously but are theoretically highly suitable for TBCs due to improved heat insulation capabilities.…”
Section: Introductioncontrasting
confidence: 45%
“…Consistently with SEM, the samples produced at 1100°C show stronger contrast, suggesting denser aggregates forming the sphere as compared to the sample prepared at 700°C. However, both samples did not present a highly dense interior [10] (which would not have allowed electron transmittance). This suggests that the heating rates of the liquid droplets were fast enough to cause precipitation from the edges of the droplets, creating a precipitation front moving inwards.…”
Section: Resultsmentioning
confidence: 99%
“…The average particle size is 0.78 jam and the standard deviation, cyn(cy . = 1 + ~/d [13], where d is the average particle size), is 1.41, respectively. The particle-size distribution of YBa2CuaOv_ x powder synthesized by the USP method has been seldom reported.…”
Section: Particle-size Distribution Of Yba2cu307_ X Powdermentioning
confidence: 99%
“…At the same time, this method has a number of drawbacks, the main of which is its low selectivity. The broad size distribution of particles produced by the plasma pyrolysis of liquid precursors is due not only to aggregation but also to the large difference in geometry between individual particles [10,11]. Ultrafine ZrO 2 -3wt.%MgO powder was used in the present studies.…”
Section: Methodsmentioning
confidence: 99%